Structure of the bacterial type II NADH dehydrogenase: a monotopic membrane protein with an essential role in energy generation. Issue 5 (21st January 2014) - Heikal, Adam; Nakatani, Yoshio; Dunn, Elyse; Weimar, Marion R.; Day, Catherine L.; Baker, Edward N.; Lott, J. Shaun; Sazanov, Leonid A.; Cook, Gregory M.
Summary Non‐proton pumping type II NADH dehydrogenase (NDH‐2) plays a central role in the respiratory metabolism of bacteria, and in the mitochondria of fungi, plants and protists. The lack of NDH‐2 in mammalian mitochondria and its essentiality in important bacterial pathogens suggests these enzymes may represent a potential new drug target to combat microbial pathogens. Here, we report the first crystal structure of a bacterial NDH‐2 enzyme at 2.5 Å resolution from Caldalkalibacillus thermarum. The NDH‐2 structure reveals a homodimeric organization that has a unique dimer interface. NDH‐2 is localized to the cytoplasmic membrane by two separated C‐terminal membrane‐anchoring regions that are essential for membrane localization and FAD binding, but not NDH‐2 dimerization. Comparison of bacterial NDH‐2 with the yeast NADH dehydrogenase (Ndi1) structure revealed non‐overlapping binding sites for quinone and NADH in the bacterial enzyme. The bacterial NDH‐2 structure establishes a framework for the structure‐based design of small‐molecule inhibitors.